Aplikasi KALFIS (Kalkulator Fisika) berbasis matlab untuk membantu analisis eksperimen fisika - Ricky Yosua; Ahmad Fauzan; Kistiani Kistiani; Irnin Agustina Dwi Astuti (Navigation Physics : Journal of Physics Education, 2019)
The purpose of this research is to produce the MATLAB-based physics Calculator application to help analyze physics experiments on the concept of mechanics. With the application of Physics calculator the student will easily analyze the physics experiments quickly and valid. The stage of the implementation consists of the preparation, the research is only in the stage of making the product is a calculator physics application. The results indicated by the KALFIS application can work well proved to be able to analyse and calculate the concepts of mechanics such as GLB, GLBB, and bullet motion.